Interrogating the Image: Movies and the World of Film and Television - Jacobs, Del (Hamilton Books, 2009)
Interrogating the Image argues that movies examining the role film and television plays in the lives of their audience have created changes both in the movies themselves and in their viewers, and considers fourteen films where the moving picture is central to the narratives. Three films discussed_The Purple Rose of Cairo, Pleasantville, and The Truman Show_offer frame-breaking experiences for their characters that allow spectators to appreciate the ruptures between lived reality and media-play, delivering therapeutic payoffs that can be restorative, reconstructive, or rejective. Other examples come from the worlds of cinema (The Majestic, Matinee, Cinema Paradiso), television (Bamboozled, Network, Natural Born Killers, Medium Cool), and the sociopolitical realm where media dominates (Being There, Wag the Dog, Bob Roberts, Bulworth). Meanwhile, significant interpretive stances_reflective/reflexive, critical, and ironic_are engendered and embraced by filmmakers and audiences who create and consume these works. The result is a media-saturated culture, in transformation and best understood using cinema's interrogative resources.